Supervision in Integrated Justice: Legal Reform and Constructive Enforcement in the Criminal Justice System - Widyawati, Anis; Arifin, Ridwan; Aisy, Rohadhatul; Abidah, Shofriya Qonitatin; Setyanto, Heru (Journal of Law and Legal Reform, 2024)
The contemporary criminal justice system faces multifaceted challenges, particularly concerning the efficacy of supervision mechanisms. This study delves into the pivotal role of supervision within the framework of integrated justice, advocating for legal reform and constructive enforcement strategies. The primary objective is to elucidate the necessity of reforming criminal execution practices to enhance the overall effectiveness and fairness of the criminal justice system. Methodologically, this study adopts a socio-legal approach, Research data were obtained from interviews, observations, interpretation of documents and materials as well as persona experience. In accordance with the constructivism paradigm and then in making observations researchers take a position as facilitators using participatory principles. Results underscore the critical need for recalibrating supervision approaches, emphasizing proactive intervention, rehabilitation, and community engagement. By synthesizing theoretical insights with practical considerations, this paper offers actionable recommendations for policymakers, law enforcement agencies, and judicial authorities to optimize supervision practices in the pursuit of justice reform.